2013
DOI: 10.1136/bjophthalmol-2013-303904
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of spectral-domain and swept-source OCT in the measurement of choroidal thickness in normal eyes

Abstract: SS-OCT permitted accurate identification of the choroido-scleral border in 100% of normal eyes, suggesting that SS-OCT was the superior modality for the measurement of CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
114
2
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(129 citation statements)
references
References 25 publications
10
114
2
3
Order By: Relevance
“…This study results regarding the subfoveal CCT in healthy controls were similar to Margolis and Spaide [12] (who used the same EDI-OCT technique) who reported a subfoveal CCT of 287 ± 76 μm in healthy subjects and Copete et al [13] who reported a subfoveal CCT of 286 ± 88μm healthy subjects using Swept Source OCT. In this study, the CCT was noted to be thinnest nasally, then increase in thickness in ascending order from the nasal to the inferior to the temporal to the superior quadrants in a circular manner also it was found to be thickest subfoveally in both groups.…”
Section: Discussionsupporting
confidence: 87%
“…This study results regarding the subfoveal CCT in healthy controls were similar to Margolis and Spaide [12] (who used the same EDI-OCT technique) who reported a subfoveal CCT of 287 ± 76 μm in healthy subjects and Copete et al [13] who reported a subfoveal CCT of 286 ± 88μm healthy subjects using Swept Source OCT. In this study, the CCT was noted to be thinnest nasally, then increase in thickness in ascending order from the nasal to the inferior to the temporal to the superior quadrants in a circular manner also it was found to be thickest subfoveally in both groups.…”
Section: Discussionsupporting
confidence: 87%
“…Copete et al 17 found similar SFCT measurements with SD-OCT with EDI compared with faster ss-OCT at 1050 nm as did Ikuno et al 18 Differences in image quality of the vitreoretinal interface between the two systems was not evaluated. Despite the perceived superior quality of choroidal imaging with 1050-nm OCT in our study, it did not seem to improve the ability to measure SFCT compared with 870 nm with EDI.…”
Section: Discussionmentioning
confidence: 90%
“…Previous reports, however, only compared the choroidal thickness measurements and did not consider the penetration of the OCT signal beyond the choroidoscleral junction, which cannot be inferred from thickness comparisons alone. 8,11,12 Choroidal thickness is an important factor in determining if the choroidoscleral junction can be identified by OCT, owing to the increasing distance from the external limit of the choroid to the zero-delay line of the OCT instrument in a relatively thicker choroid, or the increased light scattering induced by a thicker choroid. 11 Our study counteracts this limitation by introducing signal penetration depth as a new measure that has not been evaluated previously.…”
Section: Discussionmentioning
confidence: 99%
“…8,11,12 Choroidal thickness is an important factor in determining if the choroidoscleral junction can be identified by OCT, owing to the increasing distance from the external limit of the choroid to the zero-delay line of the OCT instrument in a relatively thicker choroid, or the increased light scattering induced by a thicker choroid. 11 Our study counteracts this limitation by introducing signal penetration depth as a new measure that has not been evaluated previously. We believe that the penetration depth of an OCT system is of higher clinical relevance because it allows conclusions to be drawn about situations of, for example, choroidal thickening beyond the normal range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation